Pengaruh Konten Iklan #IAmEmempoweredNature pada Instagram dan Brand Awareness terhadap Minat Produk Lafiye - Djachrab, Ida Rapida; Nuraini, Adzra Azzahra (Ma'soem University, 2024)
Based on the observation results, the background of this research is the increasing level of competition in the fashion world, especially Muslim fashion. One of the efforts implemented by the Muslim fashion brand Lafiye is by inviting the public to follow the #IAmEmpoweredNature advertising content on Instagram. This study aims to determine the effect of #IAmEmpoweredNature advertising content and brand awareness on interest in Lafiye products. The object of this study is the audience of the Lafiye Instagram account with a focus on the #IAmEmpoweredNature advertising content on Instagram and brand awareness on interest in Lafiye products. The research method is quantitative associative. The population is 293,000 people, using the Slovin formula, a sample of 100 people was obtained. Primary data was obtained through questionnaires, while secondary data was conducted through observation, literature studies, and documentation studies. Data analysis used correlation tests, regression, coefficient of determination, t-tests, and F-tests. The results of the study showed that partially the #IamEmpoweredNature advertising content on Instagram had a 38.4% effect on interest in Lafiye products; brand awareness had a 35.1% effect on interest in Lafiye products; and simultaneously #IAmEmpoweredNature advertising content on Instagram and brand awareness have a 45.8% influence on Lafiye product interest. our display screen.